Dr. Macnamara, 1861-1931 - Betts, Robin (Liverpool University Press, 1999)
This well-researched historical biography is the first on Dr T.J. Macnamara, the first ex-elementary teacher to win a government post. Colleague and close friend of Lloyd George, and praised by Winston Churchill, Macnamara was an educationist, journalist and Cabinet Minister. This study of his life and career makes a major contribution to educational history as well as to the history of the Liberal Party, the National Union of Teachers (NUT) and British political history generally. Fascinating details of Macnamara#x92;s pre-Parliamentary career are provided and, alongside the biographical account, the book deals with a range of major issues with which Macnamara was involved. In education, government control of school funding and the curriculum in the 1890s is considered together with the emergence of elementary school teachers as powerful public figures, the operation and decline of London#x92;s first education system (the London School Board 1870#x96;1904), and resistance (especially in Wales) to Balfour#x92;s 1902 Education Act. Defence issues feature: a view of the First World War arms race from inside the Admiralty; the Admiralty during the First World War from the standpoint of the only government minister who held the same office throughout the hostilities, working with, among others, Churchill and Balfour. Macnamara#x92;s establishment of the dole on response to the post-war economic slump, 1920#x96;22, is also considered. Important analysis is included of the fragmentation of the Liberal Party in the 1920s, leaving Macnamara as one of the last of Lloyd George#x92;s supporters.--